RENAL OSTEODYSTROPHY IN PATIENTS WITH END STAGE CHRONIC RENAL DISEASE - Mirzaeva, B.M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To study the characteristics of calcium-phosphorus metabolism in the aspect of calcification of coronary arteries in patients with stage V chronic kidney disease (CKD Vd) undergoing treatment with program hemodialysis. Material and methods: 49 patients with CKD Vd were included in the study; the duration of hemodialysis was at least 3 months. Results: The study of the parameters of phosphorus-calcium metabolism in patients with chronic kidney disease Vd revealed a significant degree of secondary hyperparathyroidism, which, in addition to increasing the level, was manifested by an increase in alkaline phosphatase activity. Secondary hyperparathyroidism was associated with an increase in the concentration of phosphate in the peripheral blood and a decrease in the concentration of calcium, which was within the lower normal range. Conclusions: In patients with chronic kidney disease Vd, significant coronary calcification was found, the severity of which correlates with a violation of phosphorus-calcium metabolism